Life lessons from Byron - Bevis, Matthew (The School of Life, 2013)
'The School of Life offers radical ways to help us raid the treasure trove of human knowledge' Independent on Sunday Born in 1788, Lord Byron was an English poet and a leading figure of the Romantic movement. A prodigious poetic gift and a scandalous private life made him famous throughout Europe, and his masterpiece, Don Juan, became the biggest-selling work of the period. He remains one of the most provocative, seductive voices of world literature. The Life Lessons series from The School of Life takes a great thinker and highlights those ideas most relevant to ordinary, everyday dilemmas. These books emphasize ways in which wise voices from the past have urgently important and inspiring things to tell us. 'thoroughly welcoming and approachable ... [Life Lessons from Byron is] a ringing affirmation of the power of poetry to reach down tot the essence, or at least the essences, of life ... If the six books in the Life Lessons series can teach even a few readers to pay passionate heed to the world - to notice things - they will have been an unquestionable success' John Banville, Prospect 'there is a good deal to be learned from these little primers' Observer